Stop and go: Antagonistic signals in the specification of the Drosophila R7 photoreceptor viewed from an evolutionary perspective. - Mavromatakis, Y.E.; Tomlinson, A. (Fly, 2012)
The Drosophila R7 photoreceptor precursor is directed to its fate by signals from adjacent cells that activate its Receptor Tyrosine Kinase (RTK) and Notch (N) signaling pathways. Counter-intuitively, the N activity both promotes and inhibits the photoreceptor fate in the R7 precursor. We offer an evolutionary perspective for this in which earlier ommatidia had fewer photoreceptors and used N to inhibit the addition of any more. When additional photoreceptors were added by evolution, an RTK signal was used to overcome the N inhibition in these cells, and these new additions potently activated N in their neighboring cells, preventing them from also responding to the RTK signal. The R7 precursor also receives this block, and requires robust RTK activation for it to become a photoreceptor. This is achieved by N transcriptionally activating a new RTK, one that is potently activated in the R7 precursor and sufficing to overcome the N inhibition. The unusually high RTK signal in R7 requires additional transduction components not needed when the signal is mild; in R7 the small GTPases Ras and Rap are both required to transduce the signal, but in other photoreceptors Ras alone suffices.